Evaluating contemporary usage of ornament in architectural identity in Indonesia : an organic architecture perspective - Utaberta, Nangkula; Bahar, Mohammad Arsyad; Nik Ab. Wahab, Nik Syazwan (2014)
This paper has the aim to identify organic architecture as one the design approach for ornament towards contemporary architectural identity in Indonesia. Ornament in architecture as one of the aesthetic elements also has an important function to create a local architectural identity (local wisdom). This study was conducted with the literature review and survey in several contemporary buildings in Indonesia. There are three important aspects that will be proposed in ornament design, like principles aspect, functions and physical form. That framework is expected to be a contribution for the knowledge of architecture and to realize the identity of contemporary architecture in Indonesia. 'Bhineka Tunggal Ika' architecture.